Positive electrode material and preparation method thereof, secondary battery and electric device

By sintering the cobalt source and/or boron source with nickel-cobalt manganese oxide, a cladding layer is formed, and the surface residual Li and residual lithium types of high-nickel ternary materials are regulated in a directional manner, which solves the problem of excess lithium on the surface caused by lithium-nickel mixed discharge, and improves the circulation performance and storage stability of the battery.

CN119786570APending Publication Date: 2025-04-08ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411977249.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

High-nickel ternary materials are prone to lithium-nickel mixed discharge during the synthesis process, resulting in excess of residual lithium on the surface, affecting the circulation performance and safety of the battery.

Method used

By sintering with nickel-cobalt-manganese oxide using a cobalt and/or boron source, excess residual lithium on the surface is consumed, and the surface residual Li and residual lithium species are formed, so that it is in an optimal equilibrium state of 200-1000 ppm.

Benefits of technology

It effectively reduces the problems caused by surface residual lithium, such as slurry gel, capacity reduction and gas production, and improves the circulation performance and storage stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786570A_ABST
    Figure CN119786570A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a positive electrode material and a preparation method thereof, a secondary battery and a power utilization device, the positive electrode material comprises a nickel cobalt manganese oxide, the chemical formula of the nickel cobalt manganese oxide is LiaNixCoyMnzO2Mb, x + y + z = 1, x is greater than or equal to 0.8, a is greater than or equal to 0.90 and less than or equal to 1.20, b is greater than or equal to 0 and less than or equal to 0.1, and M is a doping element; the coating layer is attached to at least part of the surface of the nickel-cobalt-manganese oxide, the coating layer comprises Co and / or B. The surface of the positive electrode material contains Li2CO3 and / or LiOH, and the total mass content of Li in the Li2CO3 and LiOH is smaller than or equal to 1000 ppm. In conclusion, by using the coating layer, the amount of residual Li on the surface of the ternary material of the nickel-cobalt-manganese oxide is in an optimal equilibrium state of 200-1000ppm, and the problems of slurry gel, capacity reduction, gas production and the like caused by excessive residual Li on the surface are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of batteries, and in particular, to positive electrode materials and preparation methods thereof, secondary batteries and electrical devices. Background Art

[0002] The ternary cathode material of lithium-ion battery has a high volume energy density (the compacted powder density is about 3.3g / cm 3 ) and a relatively high theoretical capacity (>270mAh / g), it has been widely used in portable power sources, power batteries, etc. However, due to the excessive addition of lithium salts during the material synthesis process, residual lithium (such as lithium hydroxide and lithium carbonate) is inevitably present on the surface of the material. The presence of residual lithium will cause gelation in the slurry preparation process of lithium batteries, and CO3 in lithium carbonate will 2- During the lithium battery cycle, it is easy to decompose and produce carbon dioxide gas, which has a huge impact on the battery. In addition, due to the high nickel ternary materials (such as nickel cobalt manganese oxide materials, Li a Ni x Co y Mn z O2M b , where x+y+z=1, x≥0.8, M is the doping element, referred to as NCM) is prone to lithium-nickel mixing, and excessive surface residual lithium will aggravate the interface side reaction between the material and the electrolyte, increase gas production and reduce capacity. Therefore, it is an urgent problem for technicians in this field to adopt effective means to control the amount of residual lithium on the surface of ternary materials. Summary of the invention

[0003] The present application uses two effective surface residual lithium regulating additives and a simple solid phase sintering method to directionally regulate the surface residual lithium amount and residual lithium type of high nickel positive electrode materials, control the surface residual lithium amount, and thus improve the slurry processing performance and capacity performance of high nickel materials.

[0004] The present application provides a positive electrode material, which includes: nickel cobalt manganese oxide, the chemical formula of which is Li a Ni x Co y Mn z O2M b, wherein x+y+z=1, x≥0.8, optionally x≥0.9, 0.90≤a≤1.20, 0≤b≤0.1, M is a doping element, optionally, M is one or more of B, Mg, Al, Si, Sr, Zr, W, Y, Ti, Co; and a coating layer attached to at least part of the surface of the nickel-cobalt-manganese oxide, the coating layer includes Co and / or B, and in the present application, a coating layer is provided on part of the surface of the nickel-cobalt-manganese oxide. Further, the surface of the positive electrode material contains Li2CO3 and / or LiOH, and the total mass content of Li in Li2CO3 and LiOH is ≤1000ppm, and further the mass ratio of Li2CO3 to LiOH is ≤1.5. Since serious lithium-nickel mixing occurs during the synthesis of nickel-cobalt-manganese oxide, a high-nickel (x ≥ 0.8) ternary material, the problem of surface residual Li is more serious. Therefore, the present application controls the residual Li on the surface of nickel-cobalt-manganese oxide to ≤ 1000 ppm and makes the mass ratio of Li2CO3 to LiOH ≤ 1.5 to directionally regulate the residual Li on the surface of high-nickel positive electrode materials and the type of residual lithium, control the surface residual Li, and thus improve the cycle performance of the battery.

[0005] In some embodiments, based on the total mass of the positive electrode material, the total mass content of Co and / or B in the coating layer is 0.01%-10.00% in a 100 nm depth region from the surface of the positive electrode material to the center of the positive electrode material. The total mass content of Co and / or B in the coating layer is tested using a combination of EDS and ICP, and the total Co / B content of the coating layer is obtained by subtracting the Co / B element mass content at the center of the particle diameter from the Co / B element mass content obtained by the ICP test.

[0006] The present application also provides a method for preparing a positive electrode material, comprising: providing a nickel-cobalt-manganese oxide, wherein the chemical formula of the nickel-cobalt-manganese oxide is Li a Ni x Co y Mn z O2M b, wherein x+y+z=1, x≥0.8, 0.90≤a≤1.20, 0≤b≤0.1, M is a doping element, wherein the surface of the nickel-cobalt-manganese oxide has Li2CO3 and LiOH; the total mass content of the Li element in Li2CO3 and LiOH and the mass ratio of Li2CO3 and LiOH are obtained; the surface of the nickel-cobalt-manganese oxide is treated with a cobalt source and / or a boron source: when the total mass content of the Li element in Li2CO3 and LiOH is greater than 1000ppm, the nickel-cobalt-manganese oxide is mixed with a cobalt source for First sintering to form a first coating layer, when the total mass content of Li in Li2CO3 and LiOH is ≤1000ppm and the mass ratio of Li2CO3 to LiOH is greater than 1.5, nickel cobalt manganese oxide or nickel cobalt manganese oxide with the first coating layer mixed with a boron source is second sintered to form a second coating layer; and a positive electrode material is obtained, wherein the total mass content of Li in Li2CO3 and LiOH on the surface of the positive electrode material is ≤1000ppm and the mass ratio of Li2CO3 to LiOH is ≤1.5. In some embodiments, the cobalt source includes one or more of Co(OH)2, CoOOH, Co(OH)3, Co3O4, Co2O3, CoO, CoCO3, and CoC2O4; the boron source includes one or more of H3BO3, H2BO3, HBO2, and B2O3. In some embodiments, the amount of boron added to the boron source is 0.5-1.5 times the difference between the mass of Li2CO3 and LiOH.

[0007] In some embodiments, based on the need to retain a portion of the Li element on the surface of the nickel-cobalt-manganese oxide, if the Li element on the surface of the nickel-cobalt-manganese oxide is too little, the Li element in the nickel-cobalt-manganese oxide will be dissolved, thereby destroying the structural stability of the nickel-cobalt-manganese oxide. For this reason, in the preparation process, before the surface of the nickel-cobalt-manganese oxide is treated with a cobalt source and a boron source, if the total mass content of the Li element in Li2CO3 and the LiOH is measured to be greater than 1000ppm, the amount of the cobalt source used is estimated to be 500ppm of the Li element on the surface of the nickel-cobalt-manganese oxide. The amount of cobalt element added to the cobalt source is 6-25 times the mass content of the total mass content of the Li element in Li2CO3 and LiOH minus 500ppm. In some embodiments, the surface of the nickel-cobalt-manganese oxide is treated with a cobalt source, including: mixing the cobalt source with the nickel-cobalt-manganese oxide to obtain a mixture; and keeping the mixture at a temperature of 550°C-750°C for 2h-10h in an air or oxygen atmosphere. In some embodiments, treating the surface of nickel cobalt manganese oxide with a boron source includes: mixing a boron source with nickel cobalt manganese oxide or nickel cobalt manganese oxide having a first coating layer to obtain a mixture; and keeping the mixture at a temperature of 200°C-400°C for 2h-10h in an air or oxygen atmosphere.

[0008] Some other embodiments of the present application provide a secondary battery, characterized in that it includes a positive electrode plate, and the positive electrode plate includes a positive electrode material according to any one of claims 1 to 5. Some other embodiments of the present application provide an electric device, characterized in that it includes a secondary battery according to claim 12.

[0009] In summary, by using cobalt source or boron source as an additive to precisely control the residual Li content on the surface of the ternary material, the residual Li content on the surface of the nickel-cobalt-manganese oxide ternary material is in the optimal equilibrium state of 200-1000ppm, and the mass ratio of Li2CO3 to LiOH is ≤1.5, which reduces the problems of slurry gel, capacity reduction, gas production, etc. caused by excessive residual lithium on the surface. At the same time, the first and second coating layers formed on the surface of the material after the additive is sintered can isolate the positive electrode material from contact with air or electrolyte, improve the ionic conductivity of the material and thus increase the capacity, while still improving the storage and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0010]

[0013] The corresponding aspects of the embodiments of the present disclosure are best understood from the following detailed description when read in conjunction with the accompanying drawings.

[0011] Figure 1 A scanning electron microscope image of the positive electrode material of Example 1 is shown.

[0012] Figure 2 A scanning electron microscope image of the positive electrode material of Example 2 is shown. DETAILED DESCRIPTION

[0013] As described in the background technology, excessive residual lithium on the surface of ternary materials (such as nickel-cobalt-manganese oxide) will cause gelation problems in the slurry preparation process of lithium batteries, affecting the processing of pole pieces; and, during the operation of the battery, the presence of residual lithium will aggravate the side reaction between the electrolyte and the ternary materials, affecting the battery performance, especially high-nickel ternary materials, which are prone to lithium-nickel mixing. Excessive surface residual lithium will aggravate the interfacial side reaction between the material and the electrolyte, aggravating the deterioration of battery performance.

[0014] Therefore, the excessive surface residual Li (1000-4000ppm) of the existing ternary materials not only causes the capacity and cycle performance to decrease, but also causes the positive electrode slurry to gel, affecting the processing of the pole piece. Therefore, the production process of ternary materials, especially high-nickel ternary materials, generally requires the addition of a water washing process to remove excessive lithium carbonate and lithium hydroxide on the surface of the material. Specifically, for high-nickel ternary materials, the industry usually removes excessive residual lithium on the surface of the material through a water washing process after the NCM material is obtained by sintering (mixed sintering of nickel-cobalt-manganese precursor and lithium salt). However, the water washing step leads to an increase in the investment in related equipment, an increase in the cost of material preparation, and it is difficult to accurately control the amount of residual Li on the surface of the existing water washing technology. For example, excessive water washing, while removing the residual lithium on the surface of the NCM obtained by sintering, is prone to over-washing, resulting in the dissolution of Li in the bulk phase of the material, reducing the capacity of the material. It can be seen that the increase in the water washing step leads to an increase in the investment in related equipment, an increase in material costs, and it is difficult to accurately control the amount of residual Li on the surface of the existing water washing technology, and it is easy to over-wash, resulting in the dissolution of Li in the bulk phase of the material, which reduces the capacity.

[0015] The present application uses a cobalt source and / or a boron source to sinter with a fired nickel-cobalt-manganese oxide to consume the excess residual lithium on the surface of the nickel-cobalt-manganese oxide, and directionally regulates the residual Li amount and type of residual lithium on the surface of the nickel-cobalt-manganese oxide to control the residual Li amount on the surface to be in a preferred equilibrium state. The above method is also provided to prepare an NCM material, which includes a nickel-cobalt-manganese oxide and a coating layer doped with B and / or Co formed on the surface of the nickel-cobalt-manganese oxide, and the total mass content of residual lithium elements on the surface of the above material is ≤1000ppm, and further optionally, the mass ratio of the Li2CO3 to the LiOH is ≤1.5, or the total content of Li elements on the surface of the positive electrode material is ≤500ppm, thereby improving battery performance.

[0016] Optionally, in the present application, the nickel-cobalt-manganese oxide used is a high-nickel ternary material (Ni molar ratio ≥ 0.8 (ie, x ≥ 0.8)), which is a once sintered and unwashed ternary material and has no coating layer on its surface.

[0017] Specifically, the present application provides a positive electrode material, which includes: nickel cobalt manganese oxide, the chemical formula of which is Li a Ni x Co y Mn z O2M b, wherein x+y+z=1, x≥0.8, optionally x≥0.9, 0.90≤a≤1.20, 0≤b≤0.1, M is a doping element, optionally, M is one or more of B, Mg, Al, Si, Sr, Zr, W, Y, Ti, Co; and a coating layer attached to at least part of the surface of the nickel-cobalt-manganese oxide, the coating layer includes Co and / or B, and in the present application, a coating layer is provided on part of the surface of the nickel-cobalt-manganese oxide. Further, the surface of the positive electrode material contains Li2CO3 and / or LiOH, and the total mass content of Li in Li2CO3 and LiOH is ≤1000ppm, and further the mass ratio of Li2CO3 to the LiOH is ≤1.5. Since serious lithium-nickel mixing occurs during the synthesis of nickel-cobalt-manganese oxide, a high-nickel (x ≥ 0.8) ternary material, the problem of surface residual Li is more serious. Therefore, the present application controls the residual Li on the surface of nickel-cobalt-manganese oxide to ≤ 1000 ppm and makes the mass ratio of Li2CO3 to LiOH ≤ 1.5 to directionally regulate the residual Li on the surface of high-nickel positive electrode materials and the type of residual lithium, control the surface residual Li, and thus improve the cycle performance of the battery.

[0018] Furthermore, the coating layer attached to at least a portion of the surface of the nickel-cobalt-manganese oxide is Li m CoO x and / or Li n BO y (wherein, 0.20≤m≤1.30, 0.20≤n≤1.30, 1≤x≤2, 2≤y≤3) is the main component, and the core element (Co and / or B in this application) other than Li / O element in the coating layer has a mass percentage of 0.01%-10.00%. Specifically, based on the total mass of the positive electrode material, in the 100nm depth region from the surface of the positive electrode material to the center of the positive electrode material, the total mass content of Co and / or B in the coating layer is 0.01%-10.00%. The test method of the coating amount is as follows:

[0019] Step 1: Confirm the existence of the coating layer: In the area from the surface of the positive electrode material to the center of the positive electrode material at a depth of 100nm, if the mass content of Co and / or B in the coating layer is more than 0.01% higher than the mass content of Co and / or B at the center of the material diameter, then the coating layer is considered to exist. Specifically, in the annular area along the circumference from the outer surface to the center of the positive electrode material particle cross section at 100nm, using EDS (surface scan) to test that the Co / B element content in the surface annular area is more than 0.01% higher than the content at the center of the particle diameter, then it is considered that there is Co / B element enrichment, that is, the coating layer exists;

[0020] Step 2: Confirm the coating content: ICP (inductively coupled plasma) tests the mass content of Co and B elements in the positive electrode material, where the mass content of Co and / or B elements is 0.01%-10.00% higher than the mass content of the elements at the center of the particle diameter in step 2. At this time, the mass content of Co and / or B elements is determined to be 0.01%-10.00%.

[0021] It should be noted that the above method assumes that the distribution of elements in the nickel-cobalt-manganese oxide is uniform except for the coating layer, so the content of Co and B at the center of the material represents the content of Co and B in the nickel-cobalt-manganese oxide excluding the coating layer. In addition to the above method, the content of B and Co in the coating layer can be determined according to the characteristics of the material actually tested. For example, if the coating layer contains B, the nickel-cobalt-manganese oxide (excluding the coating layer) itself does not contain B. In the B content test, the B content of the material directly tested by ICP can be considered as the B content in the coating layer.

[0022] The test method of Co and B in the coating layer can be designed according to the actual requirements of the test object and environment, and the present invention does not set any limitation.

[0023] Some other embodiments of the present application also provide a method for preparing a positive electrode material, comprising: providing a nickel-cobalt-manganese oxide, wherein the chemical formula of the nickel-cobalt-manganese oxide is Li a Ni x Co y Mn z O2M b, wherein x+y+z=1, x≥0.8, 0.90≤a≤1.20, 0≤b≤0.1, M is a doping element, wherein the surface of the nickel-cobalt-manganese oxide has Li2CO3 and LiOH; the total mass content of the Li element in Li2CO3 and LiOH and the mass ratio of Li2CO3 and LiOH are obtained. In the present application, the type and mass content of the initial residual lithium on the surface of the nickel-cobalt-manganese oxide are determined by titration. Afterwards, the surface of the nickel-cobalt-manganese oxide is treated with at least one of a cobalt source and a boron source: when the total mass content of the Li element in Li2CO3 and LiOH is greater than 1000ppm, the nickel-cobalt-manganese oxide is mixed with a cobalt source for a first sintering to form a first coating layer, and when the total mass content of the Li element in Li2CO3 and LiOH is less than 1000ppm and the mass ratio of Li2CO3 to LiOH is greater than 1.5, the nickel-cobalt-manganese oxide or the nickel-cobalt-manganese oxide formed with the first coating layer is mixed with a boron source for a second sintering to form a second coating layer. Afterwards, a positive electrode material is obtained, wherein the total mass content of Li element in Li2CO3 and LiOH on the surface of the positive electrode material is ≤1000ppm and the mass ratio of Li2CO3 to LiOH is ≤1.5. In some embodiments, treating the surface of nickel cobalt manganese oxide with a cobalt source comprises: mixing a cobalt source with nickel cobalt manganese oxide to obtain a mixture; and keeping the mixture at a temperature of 550°C-750°C for 2h-10h in an air or oxygen atmosphere. In some embodiments, treating the surface of nickel cobalt manganese oxide with a boron source comprises: mixing a boron source with nickel cobalt manganese oxide or a nickel cobalt manganese oxide formed with a first coating layer to obtain a mixture; and keeping the mixture at a temperature of 200°C-400°C for 2h-10h in an air or oxygen atmosphere.

[0024] Specifically, ① if the total mass content of Li element in Li2CO3 and LiOH on the surface of nickel-cobalt-manganese oxide (i.e., the mass fraction of residual Li element on the surface) is greater than 1000 ppm, a Co (cobalt) source needs to be added to consume excess residual Li, that is, the surface of the nickel-cobalt-manganese oxide is treated with a Co source, and the specific steps are: adding a cobalt source in an amount of 8.0-25.0 according to the mass ratio of the Co element to the total mass content of Li element in Li2CO3 and LiOH to be removed from the surface of the nickel-cobalt-manganese oxide and the above-mentioned nickel-cobalt-manganese oxide Li a Ni x Co y Mn z O2M bMix evenly, keep warm at 550-750℃ for 2-10h in air or oxygen atmosphere, so as to form the first coating layer on the nickel-cobalt-manganese oxide and make the total amount of residual Li on the surface ≤1000ppm. In the optional scheme, if the Co source is treated, the Li2CO3 and LiOH on the surface of the treated nickel-cobalt-manganese oxide are tested. If the mass ratio of Li2CO3 to LiOH is greater than 1.5, it is necessary to add B (boron) source to consume excess Li2CO3. Add B element at 0.5-1.5 times the mass difference between Li2CO3 and LiOH and mix with the nickel-cobalt-manganese oxide Li2CO3 with the first coating layer formed above. a Ni x Co y Mn z O2M b Mix evenly, keep warm at 200-400°C for 2-10h in air or oxygen atmosphere, so as to form a second coating layer, and obtain a target material with a total surface residual Li of ≤1000ppm and a mass ratio of Li2CO3 to LiOH of ≤1.5. In some cases, when the total surface residual Li is ≤500ppm after Co source treatment, B source can be optionally used for treatment or not, because the content of Li2CO3 on the surface of the positive electrode material is relatively small at this time, and the impact on the battery is small.

[0025] ② If the total mass content of Li in Li2CO3 and LiOH on the surface of nickel-cobalt-manganese oxide (i.e., the mass fraction of residual Li on the surface) is ≤1000ppm, and the mass ratio of Li2CO3 to LiOH is >1.5, then it is necessary to directly add B source to consume excess Li2CO3. Add B element at 0.5-1.5 times the mass difference between Li2CO3 and LiOH and mix with the above nickel-cobalt-manganese oxide Li a Ni x Co y Mn z O2M b The mixture is mixed evenly and kept warm at 200-400°C for 2-10 hours in air or oxygen atmosphere, thereby directly forming a second coating layer on the surface of the nickel-cobalt-manganese oxide and obtaining a target material with a total surface residual Li of ≤1000ppm and a mass ratio of Li2CO3 to LiOH of ≤1.5.

[0026] In the above embodiments, the cobalt source includes one or more of Co(OH)2, CoOOH, Co(OH)3, Co3O4, Co2O3, CoO, CoCO3, CoC2O4; the boron source includes one or more of H3BO3, H2BO3, HBO2, B2O3. That is, when the surface of the nickel cobalt manganese oxide is treated with a cobalt source and / or a boron source, the raw materials are a cobalt source (one or more of Co(OH)2, CoOOH, Co(OH)3, Co3O4, Co2O3, CoO, CoCO3, CoC2O4), a boron source (one or more of H3BO3, H2BO3, HBO2, B2O3) and the nickel cobalt manganese oxide Li a Ni x Co y Mn z O2M b . According to the different initial residual Li content on the surface of nickel-cobalt-manganese oxide (usually 200ppm-4000ppm), different additives are selected to adjust the surface residual Li content to ≤1000ppm and the mass ratio of Li2CO3 to LiOH to ≤1.5. The key is: when the initial residual Li content on the surface of nickel-cobalt-manganese oxide is ≥1000ppm, select Co source as the additive, and Co source can consume surface lithium carbonate and lithium hydroxide at the same time; when the mass ratio of Li2CO3 to LiOH in the residual Li on the surface of nickel-cobalt-manganese oxide is ≥1.5 at the initial stage of nickel-cobalt-manganese oxide or after Co source treatment, select B source as the additive, and B source preferentially reacts with CO3 at high temperature. 2- The reaction generates a second coating layer on the surface, so the B source can consume Li2CO3 in a targeted manner; ultimately, the total residual Li content on the surface of the material is controlled to be ≤1000ppm (referring to the total mass content of Li element in Li2CO3 and LiOH), and the mass ratio of Li2CO3 to LiOH is ≤1.5.

[0027] Optionally, based on the need to retain a portion of the Li element on the surface of the nickel-cobalt-manganese oxide, if there are too few Li elements on the surface of the nickel-cobalt-manganese oxide, the Li element in the nickel-cobalt-manganese oxide will be dissolved, thereby destroying the structural stability of the nickel-cobalt-manganese oxide. For this reason, in the preparation process, before the surface of the nickel-cobalt-manganese oxide is treated with a cobalt source and a boron source, if the total mass content of the Li element in Li2CO3 and the LiOH is measured to be greater than 1000ppm, the amount of the cobalt source used is estimated to be retained on the surface of the nickel-cobalt-manganese oxide. The Co (cobalt) source includes CoOOH and Co (OH) 2, and the mass of the added Co element is 8-10 times the mass of the residual Li to be removed (the total mass content of the Li element in the surface of the nickel-cobalt-manganese oxide Li2CO3 and LiOH minus 500ppm (500ppm can be considered as the target mass content)); the B (boron) source includes H3BO3, and the mass of the added B element is 0.5-1 times the difference between the mass of Li2CO3 and LiOH. Optionally, the sintering conditions for consuming residual Li by Co source are: 600-700°C for 6 hours in an oxygen atmosphere; the sintering conditions for consuming Li2CO3 by B source are: 200-300°C for 6 hours in an oxygen atmosphere. Optionally, the residual Li content on the surface of the final target core material (the total mass content of Li2CO3 on the surface of nickel-cobalt-manganese oxide and Li in LiOH) is 500-1000ppm, and the mass ratio of Li2CO3 to LiOH is ≤1.0.

[0028] In the present application, the SEM (scanning electron microscope) results show that the additive reacts with the residual Li on the surface after sintering to form a coating layer on the surface of the nickel-cobalt-manganese oxide, and the coating layer is uniformly dotted or film-like on the surface of the positive electrode material. In addition, through EDS (energy dispersive X-ray spectrometer) and ICP testing, in some embodiments, CP (argon ion polishing technology) testing can be optionally used to obtain that the surface of the material has Co or B element enrichment, and combined with the element mass content test results of ICP, it can be seen that the mass percentage of the element in the 100nm depth area from the surface of the positive electrode material to the center of the positive electrode material is 0.01%-10.00% higher than the Co or B element in the range of 100nm as the radius of the midpoint of the diameter of the positive electrode material particle. Further, the titration method tests that the residual Li mass ratio on the surface of the material is ≤1000ppm, and the mass ratio of Li2CO3 to LiOH is ≤1.5.

[0029] In summary, by using cobalt source or boron source as an additive to precisely control the residual Li content on the surface of the ternary material, the residual Li content on the surface of the nickel-cobalt-manganese oxide ternary material is in the optimal equilibrium state of 200-1000ppm, and the mass ratio of Li2CO3 to LiOH is ≤1.5, which reduces the problems of slurry gel, capacity reduction, gas production, etc. caused by excessive residual lithium on the surface. At the same time, the first and second coating layers formed on the surface of the material after the additive is sintered can isolate the positive electrode material from contact with air or electrolyte, improve the ionic conductivity of the material and thus increase the capacity, while still improving the storage and cycle stability.

[0030] In addition, some other embodiments of the present application provide a secondary battery and a corresponding power-consuming device. The positive electrode of the secondary battery includes the above-mentioned positive electrode material. The secondary battery can be a non-aqueous electrolyte lithium battery or a solid-state battery. Taking the non-aqueous electrolyte lithium battery as an example, the secondary battery includes a positive electrode plate, wherein the positive electrode plate includes the above-mentioned positive electrode material. Further, the preparation process of the secondary battery is as follows:

[0031] (1) Preparation of positive electrode sheet

[0032] The prepared positive electrode material, conductive agent, and binder are mixed in a suitable amount of NMP (N-methylpyrrolidone) solvent to form a conductive glue according to the mass ratio commonly used in the art (such as a mass ratio of 90:5:5), and then the positive electrode material is added to the conductive glue in proportion, and a homogenizer is used to mix evenly to form a positive electrode slurry, and the positive electrode slurry is applied to the positive electrode collector to form a positive electrode material layer, thereby obtaining a positive electrode sheet. In some embodiments, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, etc. Among them, the thickness of the positive electrode collector is, for example, 8μm to 15μm. In this embodiment, the positive electrode collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive electrode current collector has two oppositely disposed surfaces along its own thickness direction, and the positive electrode material layer can be disposed on the surface on either side thereof, or on both surfaces.

[0033] As an example, the positive electrode binder is selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The positive electrode conductive agent is selected from one or at least two of conductive carbon black (Super P), acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. The ratio of the positive electrode material, the conductive agent and the binder in the positive electrode material layer can be set according to the conventional settings in the art.

[0034] (2) Preparation of negative electrode sheet

[0035] The negative electrode material, negative electrode conductive agent, binder and thickener are dispersed in a solvent to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the surface of the negative electrode current collector. After drying, cold pressing and other processes, a negative electrode material layer is formed on the negative electrode current collector to obtain a negative electrode sheet. The ratio between the components in the negative electrode slurry can be set with reference to the conventional ratio, and is not limited here. In some embodiments, the negative electrode material is the negative electrode material on the negative electrode current collector as conventionally understood in the art. The type of negative electrode material can be carbon material, silicon material, lithium metal or "composite material of carbon material and silicon material", and the carbon material can be natural graphite, artificial graphite, soft carbon, hard carbon, etc.; silicon material such as elemental silicon, silicon oxide compound, silicon carbon compound, etc. The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The negative electrode binder is selected from one or a combination of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid, lithium polyacrylate, fluororubber, and PVDF; the thickener can be sodium carboxymethyl cellulose (CMC-Na).

[0036] (3) Preparation of electrolyte

[0037] The electrolyte infiltrates the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, lithium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting lithium ions. The electrolyte can be selected from conventional combinations in the art.

[0038] In one embodiment, the electrolyte includes an organic solvent and a lithium salt, wherein the organic solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), etc. The lithium salt may be selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate), LiTFOP (lithium tetrafluorooxalatophosphate), or a combination thereof in any proportion. The molar concentration of lithium salt in the electrolyte is 0.5 mol / L to 2 mol / L. In other embodiments, some film-forming additives and functional additives that can improve battery performance may be added to the electrolyte, for example, vinylene carbonate (VC), 1,3-propane sultone (PS), dithiothreitol (DTD), etc., and those skilled in the art may select them according to actual needs.

[0039] (4) Preparation of diaphragm

[0040] In some embodiments, the separator is disposed between the positive electrode plate and the negative electrode plate to play an isolating role. The separator may be, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film, a polyethylene film or a composite film. The thickness of the separator is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0041] (5) Preparation of secondary batteries

[0042] The positive electrode sheet, separator and negative electrode sheet are sequentially placed into a mold for assembly; after assembly, the electrolyte is injected, and after formation and packaging, a lithium-ion secondary battery with a ternary positive electrode material is obtained.

[0043] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.

[0044] The reagents and raw materials used in the present invention are commercially available.

[0045] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0046] Example 1

[0047] Preparation of cathode materials

[0048] Provide ternary material LiNi 0.93 Co 0.04 Mn 0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual Li mass is measured to be 2487ppm, and the excess residual Li amount to be removed is 1987ppm (2487ppm-500ppm).

[0049] Add Co element in an amount of 10 times the amount of residual Li to be removed to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the added amount of Co element is 2.0wt%. After the cobalt source Co(OH)2 is evenly mixed with the above-mentioned ternary material, the mixture is kept at 600°C in an oxygen atmosphere for 6 hours.

[0050] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 493ppm<1000ppm, of which Li2CO3 was 1703ppm and LiOH was 596ppm. The mass ratio of Li2CO3 / LiOH was 2.9>1.5, and the mass difference between Li2CO3 and LiOH was 1107ppm.

[0051] as follows Figure 1 As shown, Figure 1 A partial scanning electron microscope image of a positive electrode material 100 of LiCoO2 102 with small particles of a first coating layer formed on the surface of a nickel-cobalt-manganese oxide 101 is shown. Specifically, Figure 1 The surface morphology of the nickel-cobalt-manganese oxide 101 sintered with the cobalt source Co(OH)2 is shown. It can be seen that a first coating layer of small particles of LiCoO2 102 is formed on at least part of the surface of the nickel-cobalt-manganese oxide 101.

[0052] Example 2

[0053] The preparation method is consistent with that in Example 1, except that in Example 2, a titration method is used to test the type and mass of residual Li on the surface of the ternary material after Co treatment. The total amount of residual Li on the surface is 493ppm<1000ppm, of which Li2CO3 is 1703ppm, LiOH is 596ppm, the mass ratio of Li2CO3 / LiOH = 2.9>1.5, and the mass difference between Li2CO3 and LiOH is 1107ppm. Afterwards, B source H3BO3 is used for treatment, that is, B element with a mass of 1 times the mass difference between Li2CO3 and LiOH is added to the above-mentioned ternary material, that is, the amount of B element added is 0.11wt%. After mixing evenly, the material is kept at 300°C in an oxygen atmosphere for 6h to obtain the target positive electrode material.

[0054] See below Figure 2 , Figure 2 A partial scanning electron microscope image of a positive electrode material 100 is shown in which a first coating layer of small particles of LiCoO2 102 and a second coating layer of small particles of LiBO2 103 are formed on the surface of a nickel-cobalt-manganese oxide 101. It can be seen that Figure 2 The surface morphology of nickel cobalt manganese oxide 101 after sintering with cobalt source Co(OH)2 and boron source H3BO3 is shown. It can be seen that at least part of the surface of nickel cobalt manganese oxide 101 is formed with small particles of LiCoO2 102 of the first coating layer and small particles of LiBO2 103 of the second coating layer.

[0055] Example 3

[0056] The preparation method is consistent with that in Example 1, except that in Example 3, the amount of Co element added is 1.2wt%. The cobalt source CoOOH is evenly mixed with the above-mentioned ternary material and then heated at 650°C in an oxygen atmosphere for 8h. The total amount of residual Li on the surface is 923ppm<1000ppm, wherein the mass ratio of Li2CO3 / LiOH=1.3<1.5, thereby obtaining the target positive electrode material.

[0057] Example 4

[0058] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 4. 0.93 Co 0.04 Mn 0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual Li mass is measured to be 2487ppm, and the excess residual Li amount to be removed is 1987ppm (2487ppm-500ppm).

[0059] Add 15 times the amount of Co element required to remove residual Li to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the amount of Co element added is 3.0wt%. After the cobalt source Co2O3 and the above-mentioned ternary material are evenly mixed, they are kept at 600°C in an oxygen atmosphere for 6 hours.

[0060] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 630ppm<1000ppm, of which Li2CO3 was 1745ppm and LiOH was 1027ppm. The mass ratio of Li2CO3 / LiOH was 1.7>1.5, and the mass difference between Li2CO3 and LiOH was 718ppm.

[0061] Example 5

[0062] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 5. 0.93 Co 0.04 Mn 0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual Li mass is measured to be 2487ppm, and the excess residual Li amount to be removed is 1987ppm (2487ppm-500ppm).

[0063] Add 15 times the amount of Co element required to remove residual Li to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the amount of Co element added is 3.0wt%. After the cobalt source Co2O3 and the above-mentioned ternary material are evenly mixed, they are kept at 600°C in an oxygen atmosphere for 6 hours.

[0064] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 630ppm<1000ppm, of which Li2CO3 was 1745ppm and LiOH was 1027ppm. The mass ratio of Li2CO3 / LiOH was 1.7>1.5, and the mass difference between Li2CO3 and LiOH was 718ppm.

[0065] Afterwards, B source H2BO3 was used for treatment, that is, 0.7 times the mass of B element of the difference between Li2CO3 and LiOH was added to the above-mentioned ternary material, that is, the amount of B element added was 0.05wt%. After mixing evenly, the mixture was kept at 300°C in an oxygen atmosphere for 6 hours to obtain the target positive electrode material.

[0066] Example 6

[0067] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 6. 0.93 Co 0.04 Mn0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual Li mass is measured to be 2487ppm, and the excess residual Li amount to be removed is 1987ppm (2487ppm-500ppm).

[0068] Add 20 times the amount of Co element required to remove residual Li to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the amount of Co element added is 4.0wt%. After the cobalt source CoC2O4 is evenly mixed with the above-mentioned ternary material, keep it at 600°C in an oxygen atmosphere for 6 hours.

[0069] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 581ppm<1000ppm, of which Li2CO3 was 2128ppm and LiOH was 608ppm. The mass ratio of Li2CO3 / LiOH was 3.5>1.5, and the mass difference between Li2CO3 and LiOH was 1520ppm.

[0070] Example 7

[0071] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 7. 0.93 Co 0.04 Mn 0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual Li mass is measured to be 2487ppm, and the excess residual Li amount to be removed is 1987ppm (2487ppm-500ppm).

[0072] Add 20 times the amount of Co element required to remove residual Li to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the amount of Co element added is 4.0wt%. After the cobalt source CoC2O4 is evenly mixed with the above-mentioned ternary material, keep it at 600°C in an oxygen atmosphere for 6 hours.

[0073] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 581ppm<1000ppm, of which Li2CO3 was 2128ppm and LiOH was 608ppm. The mass ratio of Li2CO3 / LiOH was 3.5>1.5, and the mass difference between Li2CO3 and LiOH was 1520ppm.

[0074] Afterwards, B source B2O3 was used for treatment, that is, a B element with a mass that is 1 times the difference between the mass of Li2CO3 and LiOH was added to the above-mentioned ternary material, that is, the amount of B element added was 0.15wt%. After mixing evenly, the mixture was kept at 300°C in an oxygen atmosphere for 6 hours to obtain the target positive electrode material.

[0075] Example 8

[0076] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 8. 0.93 Co 0.04 Mn 0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual lithium content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual lithium mass is measured to be 2401ppm, and the excess residual lithium content that needs to be removed is 1901ppm (2401ppm-500ppm).

[0077] Add 25 times the amount of Co element required to remove residual Li to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the amount of Co element added is 4.8wt%. After the cobalt source Co(OH)2 is evenly mixed with the above-mentioned ternary material, keep it at 600°C in an oxygen atmosphere for 6 hours.

[0078] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 476ppm<1000ppm, of which Li2CO3 was 1531ppm and LiOH was 638ppm. The mass ratio of Li2CO3 / LiOH was 2.4>1.5, and the mass difference between Li2CO3 and LiOH was 893ppm.

[0079] Example 9

[0080] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 9. 0.93 Co 0.04 Mn 0.03 O2 is used as nickel-cobalt-manganese oxide, and the surface residual lithium content of the unwashed nickel-cobalt-manganese oxide ternary material is tested by titration method. The surface residual lithium mass is measured to be 2401ppm, and the excess residual lithium content that needs to be removed is 1901ppm (2401ppm-500ppm).

[0081] Add 25 times the amount of Co element required to remove residual Li to the above-mentioned nickel-cobalt-manganese oxide ternary material, that is, the amount of Co element added is 4.8wt%. After the cobalt source Co(OH)2 is evenly mixed with the above-mentioned ternary material, keep it at 600°C in an oxygen atmosphere for 6 hours.

[0082] The titration method was used to test the type and mass of residual Li on the surface of the ternary material after the Co treatment. The total amount of residual Li on the surface was 476ppm<1000ppm, of which Li2CO3 was 1531ppm and LiOH was 638ppm. The mass ratio of Li2CO3 / LiOH was 2.4>1.5, and the mass difference between Li2CO3 and LiOH was 893ppm.

[0083] Afterwards, B source H3BO3 was used for treatment, that is, 1.5 times the mass of B element of the difference between Li2CO3 and LiOH was added to the above-mentioned ternary material, that is, the amount of B element added was 0.13wt%. After mixing evenly, the mixture was kept at 300°C in an oxygen atmosphere for 6h to obtain the target positive electrode material.

[0084] Example 10

[0085] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 10. 0.65 Co 0.25 Mn 0.10 O2 is used as nickel-cobalt-manganese oxide. The surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material tested by titration is 312ppm<1000ppm, and the mass ratio of Li2CO3 / LiOH is 2.5>1.5. Therefore, B source H3BO3 is directly used for treatment, wherein Li2CO3 is 1017ppm, LiOH is 407ppm, Li2CO3 / LiOH=2.5, and the mass difference between Li2CO3 and LiOH is 610ppm.

[0086] Add 1.5 times the mass of B element of the difference between the mass of Li2CO3 and LiOH to the above ternary material, that is, the amount of B element added is 0.09wt%. After mixing evenly, keep warm at 320°C in an oxygen atmosphere for 10 hours to obtain the target positive electrode material.

[0087] Embodiment 11

[0088] The preparation method is consistent with that of Example 1, except that the ternary material LiNi is provided in Example 11. 0.65 Co 0.25 Mn 0.10 O2 is used as nickel-cobalt-manganese oxide. The surface residual Li content of the unwashed nickel-cobalt-manganese oxide ternary material tested by titration is 312ppm<1000ppm, and the mass ratio of Li2CO3 / LiOH is 2.5>1.5. Therefore, B source H3BO3 is directly used for treatment, wherein Li2CO3 is 1017ppm, LiOH is 407ppm, Li2CO3 / LiOH=2.5, and the mass difference between Li2CO3 and LiOH is 610ppm.

[0089] Add B element in an amount of about 1.2 times the mass difference between Li2CO3 and LiOH to the above-mentioned ternary material, that is, the amount of B element added is 0.07wt%. After mixing evenly, keep warm at 280°C in an oxygen atmosphere for 5h to obtain the target positive electrode material.

[0090] Comparative Example 1

[0091] The preparation method is consistent with that in Example 1, except that in Example 1, no Co source is used to treat the nickel-cobalt-manganese oxide.

[0092] Comparative Example 2

[0093] The preparation method is consistent with that in Example 1, except that the ternary material LiNi is provided in Comparative Example 2. 0.65 Co 0.25 Mn 0.10 O2 is used as nickel-cobalt-manganese oxide, and the surface residual Li of the ternary material of the unwashed nickel-cobalt-manganese oxide tested by titration is 312ppm<1000ppm, the mass ratio of Li2CO3 / LiOH=2.5>1.5, and the nickel-cobalt-manganese oxide is not treated with a cobalt source and a boron source. The following Table 1 shows the corresponding raw materials and parameters of the above Examples 1-11 and Comparative Examples 1-2.

[0094] Table 1 Corresponding raw materials and parameters of the above examples 1-11 and comparative examples 1-2

[0095]

[0096]

[0097] The positive electrode materials in the above examples 1-11 and comparative examples 1-2 were prepared into button cells for testing, as follows:

[0098] Positive electrode sheet: The positive electrode materials in the above examples 1-11 and comparative examples 1-2 are used as the main positive electrode materials, and conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) are also included. The mass ratio of the positive electrode material to these substances is 95:2.5:2.5. The method for preparing the positive electrode sheet includes the following steps: firstly mix the positive electrode material, Super P, and PVDF in the above proportions, and then gradually add nitrogen methyl pyrrolidone (NMP) with high-speed stirring to prepare a positive electrode slurry with a certain viscosity. Then the prepared slurry is evenly coated on aluminum foil, placed in a blast drying oven and dried at 120°C for 10 minutes, and finally the dried electrode sheet is rolled, cut, and made into a positive electrode sheet.

[0099] Negative electrode: Use metal lithium foil as the negative electrode.

[0100] The membrane has a thickness of 8 μm to 14 μm, an air permeability of 150 s / 100 mL to 350 s / 100 mL, and a porosity of 30% to 50%.

[0101] The electrolyte is lithium salt LiPF6 with a content of 4 to 24 wt%. The mass ratio of EC, EMC, DMC and PC in the solvent is (2 to 4):(3 to 5):(2 to 4):(0 to 1). When the mass ratio is (2 to 4):(3 to 5):(2 to 4):0, it means that the solvent does not contain PC.

[0102] The prepared positive electrode sheet and the metal lithium negative electrode sheet are assembled into a 2032 button half-cell commonly used in this field.

[0103] Then the charge and discharge capacity and cycle performance of the above button battery were tested, as follows:

[0104] At room temperature of 25°C, constant current and constant voltage charging (cut-off current of 0.05C) and constant current discharge (cut-off voltage of 3.0V) were performed at 0.33C in the voltage range of 3.0-4.3V, and the button battery was cycled 100 times to obtain its electrochemical performance test results (the electrochemical workstation equipment model is Blue Electric M340A precision battery tester). The charge and discharge capacity of the first cycle and the capacity retention rate of 100 cycles were recorded (100-cycle capacity retention rate = discharge specific capacity after 100 cycles / initial discharge specific capacity*100%).

[0105] It should be noted that the wt% Co element content of the first coating layer and the wt% B element content of the second coating layer in the following Table 2 are tested using the test method described above. Specifically, the Co / B content here is the Co / B element mass content obtained by ICP test minus the Co / B element mass content at the center of the particle diameter tested by EDS.

[0106] Table 2 Test results of the above examples 1-11 and comparative examples 1-2

[0107]

[0108] It can be seen from Example 1 that by using a cobalt source as an additive for accurately controlling the amount of residual Li on the surface of the ternary material, the amount of residual Li on the surface of the ternary material of nickel-cobalt-manganese oxide is reduced, so that it is in an optimal equilibrium state of 200-1000 ppm. In addition, it can be seen from Examples 1-5 and Comparative Examples 1-2 that by using a cobalt source and / or a boron source as an additive for accurately controlling the amount of residual Li on the surface of the ternary material, in addition to reducing the amount of residual Li on the surface of the ternary material of nickel-cobalt-manganese oxide, so that it is in an optimal equilibrium state of 200-1000 ppm, the mass ratio of Li2CO3 to LiOH is ≤1.5, and optionally the mass ratio of Li2CO3 to LiOH is ≤1.0, thereby reducing the problems of slurry gelation, capacity reduction, gas production, etc. caused by excessive surface residual lithium. At the same time, the first and second coating layers formed on the surface of the material after the additive is sintered can isolate the positive electrode material from contact with air or electrolyte, thereby improving the ionic conductivity of the material and thus the capacity, while still improving the storage and cycle stability. In addition, Figure 1 shows a scanning electron microscope image of the positive electrode material of Example 1, and Figure 2 A scanning electron microscope image of the positive electrode material of Example 2 is shown.

[0109] It can be seen from Examples 1-8 that the cobalt source includes one or more of Co(OH)2, CoOOH, Co(OH)3, Co3O4, Co2O3, CoO, CoCO3, and CoC2O4; the boron source includes one or more of H3BO3, H2BO3, HBO2, and B2O3, the amount of boron element added to the boron source is 0.5-1.5 times the difference in mass between Li2CO3 and LiOH, and the amount of cobalt element added to the cobalt source is 6-25 times the mass content of the total mass content of Li element in Li2CO3 and LiOH minus 500ppm, and can be optionally 8-10 times. The surface of nickel cobalt manganese oxide is treated with a cobalt source, including: mixing a cobalt source with nickel cobalt manganese oxide to obtain a mixture; and in an air or oxygen atmosphere, the mixture is kept at a temperature of 550°C-750°C for 2h-10h; and the surface of nickel cobalt manganese oxide is treated with a boron source, including: mixing a boron source with nickel cobalt manganese oxide or nickel cobalt manganese oxide formed with a first coating layer to obtain a mixture; and in an air or oxygen atmosphere, the mixture is kept at a temperature of 200°C-400°C for 2h-10h, both of which can form a first and / or second coating layer on the surface of the nickel cobalt manganese oxide. Optionally, the Co (cobalt) source includes CoOOH and Co (OH) 2, and the mass of the added Co element is 8-10 times the mass of residual Li to be removed (the total mass content of Li element in Li2CO3 and LiOH on the surface of nickel-cobalt-manganese oxide minus 500ppm); the B (boron) source includes H3BO3, and the mass of the added B element is 0.5-1 times the difference between the masses of Li2CO3 and LiOH. Optionally, the sintering conditions for the Co source to consume residual Li are: in an oxygen atmosphere, keep warm at 600-700°C for 6h; the sintering conditions for the B source to consume Li2CO3 are: in an oxygen atmosphere, keep warm at 200-300°C for 6h, and the effect is better.

[0110] It can be seen from Examples 1-3, 4-5, 6-7 and 8-9 that the addition of Co source can indiscriminately consume the Li element in Li2CO3 and LiOH, and the addition of B source can directionally consume Li in Li2CO3, thereby reducing the mass ratio of Li2CO3 to LiOH, thereby ensuring that the mass content of Li2CO3 is reduced to below a certain range, thereby ensuring the cycle performance of the battery.

[0111] In addition, it can be seen from Examples 10-11 and Comparative Example 2 that in the battery, due to the serious lithium-nickel mixing during the synthesis of the nickel-cobalt-manganese oxide of the high-nickel (x≥0.8) ternary material, the problem of residual Li on the surface is more serious. Therefore, the residual Li on the surface of the nickel-cobalt-manganese oxide can be controlled to ≤1000ppm, and the mass ratio of Li2CO3 to LiOH can be ≤1.5 to control the residual Li on the surface of the high-nickel positive electrode material and the type of residual lithium, and control the residual Li on the surface, thereby improving the cycle performance of the battery. However, for the nickel-cobalt-manganese oxide of the low-nickel (x<0.8, such as 0.65) ternary material, the corresponding improvement effect is not obvious.

[0112] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.

Claims

1. A positive electrode material, characterized in that: include: Nickel cobalt manganese oxide, the chemical formula of the nickel cobalt manganese oxide is Li a Ni x Co y Mn z O2M b , where x+y+z=1, x≥0.8, 0.90≤a≤1.20, 0≤b≤0.1, M is a doping element; as well as A coating layer is attached to at least a portion of the surface of the nickel-cobalt-manganese oxide, wherein the coating layer comprises Co and / or B, Wherein, the surface of the positive electrode material contains Li2CO3 and / or LiOH, and the total mass content of Li element in the Li2CO3 and the LiOH is ≤1000ppm.

2. The positive electrode material according to claim 1, characterized in that The mass ratio of the Li2CO3 to the LiOH is ≤1.

5.

3. The positive electrode material according to claim 1, characterized in that The coating layer includes Li m CoO x and / or Li n BO y , where 0.20≤m≤1.30, 0.20≤n≤1.30, 1≤x≤2, 2≤y≤3.

4. The positive electrode material according to claim 1, characterized in that M is one or more of B, Mg, Al, Si, Sr, Zr, W, Y, Ti, and Co.

5. The positive electrode material according to claim 1, characterized in that Based on the total mass of the positive electrode material, in a 100 nm depth region from the surface of the positive electrode material toward the center of the positive electrode material, the total mass content of the Co and / or B in the coating layer is 0.01%-10.00%.

6. A method for preparing a positive electrode material, characterized in that: include: Provide a nickel-cobalt-manganese oxide, wherein the chemical formula of the nickel-cobalt-manganese oxide is Li a Ni x Co y Mn z O2M b , wherein x+y+z=1, x≥0.8, 0.90≤a≤1.20, 0≤b≤0.1, M is a doping element, wherein the nickel-cobalt-manganese oxide has Li2CO3 and LiOH on its surface; Measuring the total mass content of Li element in the Li2CO3 and the LiOH and the mass ratio of Li2CO3 to the LiOH; The surface of the nickel-cobalt-manganese oxide is treated with at least one of a cobalt source and a boron source: When the total mass content of Li2CO3 and the LiOH is greater than 1000 ppm, the nickel-cobalt-manganese oxide is mixed with a cobalt source for a first sintering to form a first coating layer; When the total mass content of Li element in the Li2CO3 and the LiOH is ≤1000ppm, and the mass ratio of the Li2CO3 to the LiOH is greater than 1.5, the nickel-cobalt-manganese oxide or the nickel-cobalt-manganese oxide having the first coating layer formed thereon is mixed with a boron source for a second sintering to form a second coating layer; and The positive electrode material is obtained, wherein the total mass content of Li element in the Li2CO3 and the LiOH on the surface of the positive electrode material is ≤1000ppm and the mass ratio of the Li2CO3 to the LiOH is ≤1.

5.

7. The method according to claim 6, characterized in that The cobalt source includes one or more of Co(OH)2, CoOOH, Co(OH)3, Co3O4, Co2O3, CoO, CoCO3, and CoC2O4; the boron source includes one or more of H3BO3, H2BO3, HBO2, and B2O3.

8. The method according to claim 6, characterized in that The method of treating the surface of the nickel-cobalt-manganese oxide with a cobalt source comprises: mixing a cobalt source with the nickel-cobalt-manganese oxide to obtain a mixture; and In an air or oxygen atmosphere, the mixture is kept at a temperature of 550°C-750°C for 2h-10h.

9. The method according to claim 6, characterized in that The boron source treatment on the surface of the core structure comprises: mixing a boron source with the nickel-cobalt-manganese oxide or the nickel-cobalt-manganese oxide having the first coating layer formed thereon to obtain a mixture; and In an air or oxygen atmosphere, the mixture is kept at a temperature of 200°C-400°C for 2h-10h.

10. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1-5.

11. An electrical device, characterized in that: The secondary battery according to claim 10 is included.

Citation Information

Patent Citations

  • Co / B co-cladded nickel cobalt manganese lithium ion cathode material, and preparation method thereof

    CN108807926A

  • Ternary positive electrode material, lithium ion battery positive electrode plate and application of lithium ion battery positive electrode plate

    CN113921791A

  • Positive electrode material, preparation method thereof and lithium battery

    CN117352672A

  • Positive electrode material as well as preparation method and application thereof

    CN119008887A

  • Electrode cladding material screening method, electrode material and secondary battery

    WO2023045110A1